Oregon State Building viewed across Geyser Basin, University of Washington, approximately 1911
Frosh Pond was formerly known as Geyser Basin. Today the pond contains Drumheller Fountain, built in 1961. This image shows the Oregon Building from the 1909 Alaska Yukon pacific Exposition in the background. Handwritten on verso: A.A. Peterson. PH Coll 778